Linguagem, conhecimento e hermenêutica filosófico-teológica em Santo Agostinho - Sales, Antonio Patativa de (2019)
This piece analyses the questions of knowledge and language, presented as intrinsically linked and according to the hermeneutics of St. Augustine. In De magistro, De doctrina christiana and De dialectica, in particular, the Hipponese understands that language is the main (conventional) vehicle of human communication. Thus, it endeavors to understand (and expose) the ways we use language for the transmission of meanings – the thoughts and intentions (cognitiones et voluntates) of who speaks – starting from linguistic practices and conventions, subordinating semantics to pragmatics. Its task, therefore, is to value the exposition of the doctrina christiana (sacred hermeneutics), rather than to simply and systematically base a method, a model of interpretation (philosophical hermeneutics). In this intention, the study of grammar or significant sentences (sign theory) becomes useful because, in addition to assuming an ontic-ontological order (metalanguage), it presupposes an internal logic of/in the word in/about the discourse that, well conducted-arranged, ascends from the complex to the simple, from the figuration to the intelligible Form (ηδέα), from man to God. These notions, however, are not specific of/in the Hipponese, but inherited from the Bible and the philosophical tradition (platonic, aristotelian, stoic and neoplatonic). The novelty in Augustine is to make of language, as a propositional matter, an auxiliary instrument for knowledge, which must be used in favor of faith, of doctrina christiana (vera religio, vera philosophia) – and he does so from a point of view in the first person, culminating in a protoexistentialist hermeneutic, the “grand hermeneutic in grand style”, in Heidegger‟s words.